Velaglucerase alfa enzyme replacement therapy compared with imiglucerase in patients with Gaucher disease. Issue 3 (9th February 2013) - Turkia, Hadhami Ben; Gonzalez, Derlis E.; Barton, Norman W.; Zimran, Ari; Kabra, Madhulika; Lukina, Elena A.; Giraldo, Pilar; Kisinovsky, Isaac; Bavdekar, Ashish; Dridi, Marie‐Françoise Ben; Gupta, Neerja; Kishnani, Priya S.; et al.
<x xml:space="preserve">Abstract</x> Enzyme replacement therapy for Gaucher disease (GD) has been available since 1991. This study compared the efficacy and safety of velaglucerase alfa with imiglucerase, the previous standard of care. A 9‐month, global, randomized, double‐blind, non‐inferiority study compared velaglucerase alfa with imiglucerase (60 U/kg every other week) in treatment‐naïve patients aged 3–73 years with anemia and either thrombocytopenia or organomegaly. The primary endpoint was the difference between groups in mean change from baseline to 9 months in hemoglobin concentration. 35 patients were randomized: 34 received study drug (intent‐to‐treat: 17 per arm), 20 were splenectomized. Baseline characteristics were similar in the two groups. The per‐protocol population included 15 patients per arm. The mean treatment difference for hemoglobin concentration from baseline to 9 months (velaglucerase alfa minus imiglucerase) was 0.14 and 0.16 g/dL in the intent‐to‐treat and per‐protocol populations, respectively. The lower bound of the 97.5% one‐sided confidence interval in both populations lay within the pre‐defined non‐inferiority margin of −1.0 g/dL, confirming that velaglucerase alfa is non‐inferior to imiglucerase. There were no statistically significant differences in the secondary endpoints. Most adverse events were mild to moderate. No patient receiving velaglucerase alfa developed antibodies to either drug, whereas four patients (23.5%) receiving imiglucerase developed IgG antibodies to imiglucerase, which were cross‐reactive with velaglucerase alfa in one patient. This study demonstrates the efficacy and safety of velaglucerase alfa compared with imiglucerase in adult and pediatric patients with GD clinically characterized as Type 1. Differences in immunogenicity were also observed. Am. J. Hematol. 88:179–184, 2013. © 2012 Wiley Periodicals, Inc.